In-situ observations and modeling of small nitric acid-containing ice crystals - C. Voigt (Atmospheric Chemistry and Physics, 2007)
Measurements in nascent ice forming regions are very rare and help understand cirrus cloud formation and the interactions of trace gases with ice crystals. A tenuous cirrus cloud has been probed with in-situ and remote sensing instruments onboard the high altitude research aircraft Geophysica M55 in the tropical upper troposphere. Besides microphysical and optical particle properties, water (H2O) and reactive nitrogen species (NOy) have been measured. In slightly ice supersaturated air between 14.2 and 14.9 km altitude, an unusually low ice water content of 0.031 mg m−3 and small ice crystals with mean radii of 5 µm have been detected. A high nitric acid to water molar ratio (HNO3/H2O) of 5.4×10−5 has been observed in the ice crystals, about an order of magnitude higher compared to previous observations in cirrus at temperatures near 202 K. A model describing the trapping of HNO3 in growing ice particles shows that a high HNO3 content in ice crystals is expected during early growth stages, mainly originating from uptake in aerosol particles prior to freezing. Water vapor deposition on ice crystals and trapping of additional HNO3 reduces the molar ratio to values close to the ratio of HNO3/H2O in the gas phase while the cloud ages.